Analysis of the Relationship Between Economic Growth, Inflation and Unemployment in Indonesia - KURNIAWAN, Muhammad Lukman; PUDJIHARDJO, M.; PRASETYIA, Ferry (International Journal of Environmental, Sustainability, and Social Science, 2023)
The aim of developing a country is for the welfare of society. the policy makers are currently focused on the level of economic growth, inflation and unemployment. According to theory, these variables are closely related. The porpuse of the study was to analyze the relationship between economic growth, inflation and unemployment in Indonesia. Method used Vector Error Correction Model (VECM) analysis and Granger Causality Test. The results of this research show that in the long term, inflation has a significant positive relationship with economic growth, and unemployment has a negative and insignificant relationship. In the short term, inflation has no relationship to economic growth, and unemployment has a significant relationship. The results of the causality test, economic growth, inflation and unemployment do not have interrelationship.